Does financial performance follow firm life cycle? Evidence from Indonesian firms - M Kemal Al Rasyid; Poppy Nurmayanti; Hariadi (Journal of Contemporary Accounting, 2022)
This study aims to determine whether the asset turnover ratio, current ratio, debt ratio and return on net worth influences profitability at each firm life cycle stages in manufacturing companies on the Indonesia Stock Exchange. The study only focuses on introduction stage and growth stage. The classification at each stage of the firm life stages uses the sales growth variable to categorize it. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique in this study used purposive sampling technique and obtained a sample of 36 companies. The data analysis method used is panel data multiple regression analysis. The results indicate that at introduction stage only debt ratio and return on net worth that found has a significance influences on profitability. At growth stage almost all independent variable has a significance influences on profitability, except current ratio variable.